1978
DOI: 10.1111/j.1432-1033.1978.tb12597.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline Antitumor Antibiotic · Nucleic‐Acid Interactions

Abstract: The helix-to-coil transition of the synthetic DNA poly(dA-dT) in the presence of the anthracycline antitumor antibiotic daunomycin has been investigated by high-resolution proton nuclear magnetic resonance (NMR) spectroscopy in 1 M salt solution. The dissociation of the complex, containing molar ratios of phosphate to daunomycin (Pi/drug) of 50, 25, 9 and 5, with increasing temperature can be monitored independently at the nucleic acid and the antibiotic resonances under conditions of fast exchange. The antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
13
1

Year Published

1981
1981
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 32 publications
7
13
1
Order By: Relevance
“…By contrast, previous studies from our laboratory demonstrated that the anthracycline ring D ofdaunomycin does not overlap with adjacent base pairs of poly(dA-dT), on the basis of the small (0.1-0.3 ppm) upfield complexation shifts of the nonexchangeable protons of this ring system on complex formation (9).…”
contrasting
confidence: 80%
See 1 more Smart Citation
“…By contrast, previous studies from our laboratory demonstrated that the anthracycline ring D ofdaunomycin does not overlap with adjacent base pairs of poly(dA-dT), on the basis of the small (0.1-0.3 ppm) upfield complexation shifts of the nonexchangeable protons of this ring system on complex formation (9).…”
contrasting
confidence: 80%
“…The x-ray data on the daunomycin-hexanucleotide complex demonstrate binding through the minor groove, because the sugar ring is located in this groove (8). It appears that this crystallographic observation can be extended to solution, because we have previously demonstrated that stabilization of the synthetic DNA helix by bound daunomycin is unperturbed by the introduction of bulky halogen substituents at the pyrimidine 5 position, which faces the major groove (9).…”
mentioning
confidence: 89%
“…Within this area particular attention has been directed towards the interaction of daunomycin (scheme 1) with various DNA fragments (calf thymus DNA, poly d(G-C), poly d(A-T) or shorter sequences such as d(C-G), d(G-C), d(C-G-T-A-C-G), d(A-T)3, d(G-C-G-C)), investigated by numerous techniques such as fluorescence, IR absorption, CD, X-Ray diffraction, NMR [8][9][10][11][12][13][14][15][16][17]. An X-Ray diffraction study of the crystal structure of a daunomycind(C-G-T-A-C-G) complex showed that the DNA forms a six base-pairs right handed double helix with two daunomycin intercalated in the d(C-G) sequences [8].…”
Section: Introductionmentioning
confidence: 99%
“…This mode of binding does not occur in oligodeoxynucleotides possessing A and T or G and C bases, because of intrinsic symmetry along the two directions of the DNA molecule for these polymers. The relevance for considering both these orientations was supported by various experimental observations (Patel and Canuel 1978;Klevit et al 1986;Coll et al 1987Coll et al , 1989. For this reason, in our experiments we used the two structural classes of GC polymers.…”
Section: Introductionmentioning
confidence: 89%